2010
DOI: 10.1152/ajpregu.00027.2010
|View full text |Cite
|
Sign up to set email alerts
|

Age is a determinant of acute hemodynamic responses to hyperglycemia and angiotensin II in humans with uncomplicated type 1 diabetes mellitus

Abstract: -Hyperglycemia is associated with hemodynamic changes in type 1 diabetes (DM), acting in part through renin-angiotensin system activation. Since aging is associated with vascular dysfunction in DM, we hypothesized that acute hemodynamic responses to clamped hyperglycemia and infused ANG II would be exaggerated in older adults compared with a group of adolescent/young adults with type 1 DM. Renal hemodynamic function, blood pressure, and arterial stiffness were assessed in adolescent/young adults (n ϭ 34; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…Previous studies of renal haemodynamics in diabetes have typically reported renal plasma flow rather than renal blood flow, measured by clearance studies using radioisotopes or other tracers, and a good correlation between MR and tracer studies has been reported [27]. The MRI-derived values for renal blood flow in our control participants are of the same order of magnitude as previously reported using MRI [27] and clearance methods [8]. Clearance studies have suggested increased [28] or normal [26,29] effective renal plasma flow in younger normoalbuminuric type 1 patients with relatively short disease duration.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Previous studies of renal haemodynamics in diabetes have typically reported renal plasma flow rather than renal blood flow, measured by clearance studies using radioisotopes or other tracers, and a good correlation between MR and tracer studies has been reported [27]. The MRI-derived values for renal blood flow in our control participants are of the same order of magnitude as previously reported using MRI [27] and clearance methods [8]. Clearance studies have suggested increased [28] or normal [26,29] effective renal plasma flow in younger normoalbuminuric type 1 patients with relatively short disease duration.…”
Section: Discussionsupporting
confidence: 78%
“…The pattern of flow through the renal arteries was similar in our diabetic and control groups, suggesting that the reduction in flow was not due to haemodynamically significant narrowing of the renal artery, but attributable to increased intrarenal vascular resistance. RVR, calculated from clearance of para-aminohippurate, is reduced in young type 1 diabetic patients without complications, and increases with age, independent of diabetes duration [8]. In contrast, in control participants, there is no or a very weak effect of age on RVR [8].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations